ANALISIS KEPATUHAN SYARIAH PADA PEMBIAYAAN SEPEDA MOTOR DI KSPPS USAHA MULYA JAKARTA - Afda Humairoh, (2022)
Islamic financing institutions, both Islamic banking and Islamic microfinance institutions, use murabahah contracts in every financing transaction. At present, in practice, several murabaha schemes are found that are not in accordance with sharia principles and there are deviations from murabaha schemes. Therefore, this study aims to determine sharia compliance in motorcycle financing at Islamic Microfinance Institutions to be precise at KSPPS Usaha Mulya. This research uses descriptive qualitative method. The data sources used in this study are primary data and secondary data. Data collection techniques in this study were carried out using structured interviews, passive observation, and documentation. Researchers used triangulation techniques to test the validity of the data. Researchers use data reduction, data presentation, and drawing conclusions for data analysis techniques. The results of this study indicate that the motorbike financing mechanism has five stages and sharia compliance carried out by KSPPS Usaha Mulya in motorcycle financing is in accordance with the transactions regulated in the existing OJK fatwa and regulations but there is still one thing that is not suitable, namely regarding the writing down payment in the contract agreement. Keywords: financing, KSPPS, sharia compliance